Perencanaan Mobilisasi Sampah Desa Batu Putik - Ida Ayu Oka Suwati Sideman; Ida Bagus Ketut Widiartha (CV. Multi Kreasi Media, 2024)
Batu Putik Village has carried out potential disaster mapping, and has determined the potential for disaster based on community perception, namely flood disasters that occur during the rainy season with the trigger being incomplete waste processing. There is no certainty about the waste residue that will be sent to the Ijo Balit Final Processing Site (TPA) owned by the East Lombok district government, creating obstacles for planning modes and mobilization. For this reason, it is deemed necessary to have a community assistance activity based on Participatory Action Research (PAR) which is able to design a pattern for transporting waste residues to the landfill with community involvement to maintain the continuity of the program in the future even if assistance is not provided. This activity shows that the residual waste after sorting is 1,030 tons/day so the optimal mode for transporting it is a dump truck with a capacity of 3m3 or a pick-up with a capacity of 2m3. The travel time required is around 1 hour for a travel distance of 42.29 km. It is highly recommended in further research to calculate the operational costs of Integrated Temporary Processing Sites (TPST) in villages, where waste sorting is carried out as a trigger for program sustainability, especially for TPST independence.